Structural behavior of the geothermo-electrical asphalt pavement: A critical review concerning climate change. Issue 12 (December 2022) - Al-Atroush, M.E.
Abstract: Particularly for asphalt pavement, where the temperature is a crucial driver in selecting construction materials, premature infrastructure failure and higher maintenance costs might be highly expected with the recently witnessed dramatic changes in climate. Numerous studies highlighted how the recent climate change might result in hazards to transportation infrastructure and affect all types of transportation modes. On the flip side, flexible pavement also contributes to global warming; various studies referred to the significant emissions percentages released by asphalt pavement upon subjection to solar radiation. With that in mind, several studies showed that the environmentally-friendly geothermal systems that mainly depend on heat exchanging with the soil have positive influences on reducing energy consumption, melting the ice on roadways in cold climates, or reducing the ambient temperature and the induced latent heat from the pavement in hot climates. However, very limited studies explored the influence of those geothermal systems on the structural behavior of the pavement concerning the associated distresses with extreme climate changes. In this paper, a critical review concerning climate change has been performed to investigate the structural performance and the associated distress of both conventional and geothermal asphalt pavement. This review underlines several advantageous physical and mechanical characteristics of geothermal pavement, which may recommend this system as a worthwhile alternative to conventional asphalt pavement. The paper also identified future research needs to overcome the shortcomings associated with the structural performance of the geothermo-electrical asphalt pavement. Abstract : Structural behavior of geothermal pavement; Asphalt pavement distresses; Temperature effect of pavement performance; Energy harvesting from Asphalt pavement.